Prospek Pemberlakuan RKUHP Pasca Disahkan Menjadi Undang-undang dalam Perspektif Maqasid Syariah - Moh Hatta (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
This paper aims to analyze the principles and concepts that must be done with the reform of Criminal Law in Indonesia and an overview of maqasid al-sharì'ah upon this reform. At the end of the paper, two things are concluded. First, to welcome the discussion on the Bill of the Criminal Code, several points of thought need to be considered: The adjustments to human rights and respect for freedom of expression based on the needs of modern times and should accommodate the existence of customary law. It also should emphasize that justice must take precedence over legal certainty. The Bill should emphasize that